TRAIT AND FACTOR CAREER THEORY AND ITS IMPLICATIONS IN CAREER GUIDANCE AND COUNSELING SERVICES FOR SPECIAL NEEDS LEARNERS - Hidayati, Nurul; Idhartono, Amelia Rizky; Mufidah, Elia Firda (Jurnal Konseling Pendidikan Islam, 2025)
Career development is a crucial aspect of an individual's life, particularly in the face of rapidly evolving social, economic, and cultural changes. One of the most influential approaches in career progression theory is the Trait and Factor Theory. This theory emphasizes the importance of compatibility between individual characteristics (traits) and occupational characteristics (factors). Through this theory, researchers and practitioners try to understand how individuals can choose career paths that suit their interests, personality, abilities, and existing environmental conditions. This article will outline the core concepts in Trait and Factor Theory, and the application in the career counseling process to help individuals achieve optimal career suits, including students with special needs.